LONG-TERM TRENDS OF INVESTMENT ACTIVITY IN THE RUSSIAN ECONOMY - S. N. Gusev (Russian Journal of Economics and Law)
Objective: to estimate the results of investment development of the Russian economy during market transformations in quantitative and structural aspects, as well as in comparison with similar indicators of BRIC partner countries. Methods: statistical; abstract-logical, calculating-variantive analytical method. Results: basing on the study of long-term trends of accumulation dynamics, the reasons are identified impeding intensification of investment processes in the Russian economy and strengthening its modernization potential. The key barriers, hintering the increase of efficiency of investment sphere, are such factors as increasing the capital intensity of growth, inefficient configuration of investment activity, inability of financial sector to involve national savings into investment turnover, as well as inadequate position of Russia in the system of international investment relations. Scientific novelty: by extrapolation of the long-term trends of investment development of the Russian economy observed in 1970–1980, the accumulated volumes of under-investment are calculated for the period of market transformations. It is shown that the unsatisfactory results of the investment sphere functioning are not a logical consequence of the transition period, but are predetermined by the reforms logic and state policy features in the modern history of the Russian Federation. Practical value: possibility to overview the principles and mechanisms of state regulation of accumulation processes in the Russian economy, to overcome the significant volumes of under-investment and to transit full-fledged to the model of overtaking social-economic development.